2020
DOI: 10.1073/pnas.2000304117
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric arrangement of mitochondria:plasma membrane contacts between adjacent photoreceptor cells regulated by Opa1

Abstract: Mitochondria are known to play an essential role in photoreceptor function and survival that enables normal vision. Within photoreceptors, mitochondria are elongated and extend most of the inner-segment length, where they supply energy for protein synthesis and the phototransduction machinery in the outer segment, as well as acting as a calcium store. Here, we examined the arrangement of the mitochondria within the inner segment in detail using three-dimensional (3D) electron microscopy techniques and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…The closeness and extent of the association of the cortical mitochondria with the plasma membrane suggests that some kind of contact site is formed between the mitochondrion outer membrane and the plasma membrane. This may be of the form identified in mouse rod photoreceptors 33 . We identified little evidence of the trans-cellular mitochondrial alignment described in mouse, the photoreceptors being mostly too far apart to allow apposition of such membranes.…”
Section: Discussionmentioning
confidence: 80%
“…The closeness and extent of the association of the cortical mitochondria with the plasma membrane suggests that some kind of contact site is formed between the mitochondrion outer membrane and the plasma membrane. This may be of the form identified in mouse rod photoreceptors 33 . We identified little evidence of the trans-cellular mitochondrial alignment described in mouse, the photoreceptors being mostly too far apart to allow apposition of such membranes.…”
Section: Discussionmentioning
confidence: 80%
“…The closeness and extent of the association of the cortical mitochondria with the plasma membrane suggests that some kind of contact site is formed between the mitochondrion outer membrane and the plasma membrane. This may be of the form identi ed in mouse rod photoreceptors 34 . We identi ed little evidence of the trans-cellular mitochondrial alignment described in mouse, the photoreceptors being mostly too far apart to allow apposition of such membranes.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, it has been shown that there is a close spatial association between some mitochondria and the plasma membrane in mouse photoreceptor inner segments (IS). Further, some display alignment with their neighbors in adjacent cells across the membranes and there are visible tethers between them at relatively consistent distances that appear to connect them even though they are in different cells 43 . This may suggest trans-cellular mitochondrial communication that could be the structural basis for the synchronized oscillations we reveal here.…”
Section: Discussionmentioning
confidence: 99%